Pemberdayaan Masyarakat Indragiri Hulu Melalui Guru Sekolah Dasar dalam Pembuatan Video Dokumenter Berbasis Budaya Melayu Sebagai Warisan Budaya Lokal - Mulyani, Eva Astuti; Fauza, Naila; Charlina, Charlina; Putra, Zetra Hainul; Hadriana, Hadriana; Novianti, Ria; Barokah, Rifqa Gusmida Syahrun (Unri Conference Series: Community Engagement, 2024)
The community empowerment program in Indragiri Hulu Regency involves elementary school teachers in the production of culture-based documentary videos as part of efforts to preserve local Malay cultural heritage. This initiative, conducted at SDN 005 Batu Gajah, Pasir Penyu Subdistrict, aims to enhance teachers' skills in designing and producing documentary videos focused on Malay culture. The training covers Malay culture theory, the integration of culture into education, scriptwriting techniques, cinematography, video editing, and hands-on practice. The results demonstrate a significant improvement in the teachers' technical skills, evidenced by the creation of four documentary videos: The History of Batu Gajah, The History of Danau Raja, The Making of Kue Bingke, and Silat Pasir Keranji. Although participants were enthusiastic, some encountered technical difficulties due to limited experience with video production tools, highlighting the need for further support and training. This study emphasizes the importance of documentary production training in supporting the preservation of Malay culture and enriching culturally based education. The program is expected to strengthen local curricula with relevant cultural content and reinforce cultural preservation efforts in schools and the community. It is recommended that sustainable training programs with adequate support be implemented to ensure the long-term impact of this initiative in Indragiri Hulu.